Synthesis and Characterization of Graft Copolymer Rice Straw Cellulose-Acrylamide Hydrogels Using Gamma Irradiation - D. Swantomo; Rochmadi Rochmadi; K.T. Basuki; R. Sudiyo (Atom Indonesia, 2013)
Rice straw cellulose available as waste biomass was graft copolymerized with acrylamide monomer by simultaneous gamma irradiation as initiator. The effects of bleaching of cellulose and irradiation dose were evaluated. Evidence of grafting is obtained from comparison of Fourier Transfer Infrared (FTIR) of the cellulose and grafted cellulose. X-ray diffraction analysis shows that crystallinity was reduced through graft copolymerization. Kinetic investigations of the graft copolymerization were also carried out, and the rate constant parameter (kp/kt0.5) has been found to be 4.9922 l0.5. mol-0.5.s-0.5. The results show that for the same dose, grafting efficiency is higher with the bleached cellulose form than with the unbleached form. The grafting efficiency and the gel fraction increases with increasing total irradiation doses. At higher radiation doses crosslink density starts to increase considerably while swelling degree decreases with the increasing crosslink density.Received: 16 January 2013 Revised: 3 June 2013; Accepted: 21 June 2013